A Case of Isolated Congenital Stapedial Suprastructure Fixation - Lee, Jeon Mi; Lee, Hyun Jin; Kim, Sung Huhn (Case Reports in Otolaryngology, 2022)
We report a case of conductive hearing loss caused by isolated congenital stapedial suprastructure fixation with normal footplate mobility. A 60-year-old woman visited the clinic for right-sided mixed hearing loss. Exploratory tympanotomy revealed a bony synostosis between the stapedial suprastructure and promontory, while all the ossicles were present and normally shaped. As the bony synostosis was separated, the stapes became mobile. This is the first report in the medical literature of this congenital ear anomaly. This case also illustrates that stapedial fixation can occur in the suprastructure as well as in the footplate; thus, one must be mindful of this when performing exploratory tympanotomy for stapes fixation.